Who’s on First?: Veli-Matti Kärkkäinen’s First Article Theology - Stephenson, Christopher A. (Pneuma, 2023)
The terms first, second, and third article theology are relatively new, and theologians use them equivocally. Veli-Matti Kärkkäinen’s first article theology focuses on the doctrines of God, revelation, and creation in and of themselves, that is, on theological topics broadly associated with the first article of the Creed. Another way to approach first article theology is to make a theology of the Father the perspective from which to view other systematic loci. Pentecostal theologians might benefit from such a theological inquiry, if for no other reason than as an exercise in the discipline associated with rigorous systematic thinking and as training in the kind of speculative theology that they have traditionally avoided. A methodology marked by a theology of the Father in trinitarian perspective and brought to bear upon other systematic loci might be compatible with a methodology marked by the liturgical theology axiom lex orandi, lex credendi.